Konsep Pembagian Harta Warisan Bersama Apabila Suami Atau Istri Meninggal Dunia - Tri Marno Butarbutar; Lidya Erdawati; Yeni Lisa Sitorus (CV. ITTC INDONESIA, 2024)
One common issue related to joint property between spouses arises when inheritance is opened due to divorce or death. The concept of inheritance division in joint property appears straightforward but is complex and often triggers conflicts among heirs who may question the distribution process. The implementation of this law affects financial rights, inheritance, and responsibilities during and after marriage. However, it also raises questions and challenges regarding the protection of individual assets and the division of property in case of divorce or death of one spouse. This research aims to analyze the concept of inheritance division in joint property when one spouse passes away. The article employs a literature review method with a comparative approach involving the comparison of two or more objects, phenomena, or concepts to evaluate their differences and similarities. The objective of this research is to gain a deeper understanding of these differences and similarities to address the complexity of inheritance division in joint property. Using a comparative approach, the article aims to provide insights into issues related to inheritance division in joint property, thereby offering a clearer understanding of the complexities involved.